TEMPORAL DIMENSIONS OF ACQUISITION OF PROPERTY FROM AN UNAUTHORIZED SELLER - Petro D. Guyvan (Alfred Nobel University Journal of Law)
This scientific work is dedicated to the research of the topical issue of the procedure and time of acquisition of the right of ownership in the case of acquiring a thing by purchasing it from an unauthorized seller. Such cases are not uncommon in property circulation in society, but without proper legal regulation of their mechanisms and consequences, a significant part of things will be withdrawn from property circulation. Of course, a certain role is played here by the revived institution of acquisitive prescription, but also important importance is attached to the tools of obtaining ownership at the time of occupation of the thing in accordance with the mechanism of Art. 330 of the Central Committee of Ukraine. However, this article is in significant conflict with Art. 388 of the Civil Code of Ukraine, which regulates the procedure and grounds for vindication protection of property, which is a shortcoming of the current legislation. Therefore, the work analyzes theoretical developments in the commented direction and compares them with the practical course of concrete relations when a bona fide purchaser receives an item from a person who was not supposed to alienate the property, but did so voluntarily or involuntarily. Doctrinal approaches to the consequences of such an occupation have been studied. It was established that the good faith of the illegal expropriator does not matter, the legal consequences of such a transaction are determined based on the identity of the acquirer. If he is in good faith, which is presumed, then the acquisition of the right of ownership by acquisitive prescription can occur for a person in good faith only in the case when he owns a thing that was lost, stolen or otherwise removed from authorized subjects. In all other cases, the property is immediately acquired by a bona fide person at the time of receiving the property from an unauthorized seller. However, the author does not support the indicated approach to the acquisition of property at the moment when a bona fide subject receives property from an unauthorized seller, not as a ready- made recipe, but only as a starting material for further theoretical construction. Such work was carried out in this article, specific proposals were made regarding the improvement of the current regulatory framework.